Synthetic Inlet Boundary Conditions for LES - Persson, Jim (My University, 2015)
This thesis describes the analysis of four different methods for generating synthetic turbulence, and the implementation of the methods into HYDRA CFD Code. These methods are the synthetic eddy method (SEM) by Jarrin, divergence free synthetic eddy method (DFSEM) by Poletto, synthetic fluctuations by Davidson, and a spectral method for generating fluctuations by Batten. The SEM and the DFSEM are stochastic algorithms that use the view of turbulence as a superposition of eddies, whereas the last two methods use the Fourier space to describe turbulence in terms of wavenumbers. The motivation of this work is the growing interest of using unsteady simulations, in particular large eddy simulations (LES), in engineering applications, and the computational issues that come with it. In order to use LES, instantaneous inlet velocities are needed as turbulent in flow boundary conditions. These boundary conditions will be given by synthetic turbulence, generated by the four methods mentioned. The object is to trigger the equations to start resolve turbulence. The methods are first implemented in C and investigated in terms of correlation in space and time for the generated turbulence. It is shown that all of the methods generated fluctuations with proper correlation in time and space. Next, the SEM, the DFSEM, and the synthetic fluctuations method are implemented into the CFD programming language HYDRA CFD Code. Last, the implementation of the SEM and the DFSEM is further investigated through a channel flow simulation in HYDRA, where the two methods are used for generating inlet conditions. The results from these simulations show that the SEM and the DFSEM produces fluctuations that remain throughout the channel.
Keywords: Transport; Strömningsmekanik; Transport; Fluid mechanics